Genomics reveals zoonotic and sustained human mpox spread in West Africa - Edyth Parker; Ifeanyi F. Omah; Delia Doreen Djuicy; Andrew Magee; Christopher H. Tomkins-Tinch; James Richard Otieno; Patrick Varilly; Akeemat Opeyemi Ayinla; Ayotunde E. Sijuwola; Muhammad I. Ahmed; Oludayo O. Ope-Ewe; Olusola Akinola Ogunsanya; et al. (Nature, 2025)
Abstract Five years before the 2022 multi-country mpox outbreak, Nigeria and Cameroon reported their first cases in more than three decades1,2. Whereas the outbreak in Nigeria is recognized as an ongoing human epidemic, the drivers of the resurgence in Cameroon remain unclear3,4. The rate of zoonoses remains uncertain in both countries, and gaps in genomic data obscure the timing and zoonotic and geographic origin of monkeypox virus (MPXV) emergence in humans. Here, to address these uncertainties, we sequenced 118 MPXV genomes isolated from cases in Nigeria and Cameroon between 2018 and 2023. We show that in contrast to cases in Nigeria, cases in Cameroon are the result of repeated zoonoses, with two distinct zoonotic lineages circulating across the Nigeria–Cameroon border. Our findings suggest that shared animal populations in the cross-border forest ecosystems drive the emergence and spread of the virus. Accordingly, we identify the closest zoonotic outgroup to the Nigerian human epidemic lineage (hMPXV-1) in a southern Nigerian border state. We estimate that the shared ancestor of the zoonotic outgroup and hMPXV-1 circulated in animals in southern Nigeria in late 2013. We find that hMPXV-1 emerged in humans in August 2014 in the southern Rivers State and circulated undetected for three years. Rivers State was the main source of viral spread during the human epidemic. Our study sheds light on the recent establishment of MPXV in the human population and highlights the risk of persistent zoonotic emergence of MPXV in the complex border regions of Cameroon and Nigeria.